Decadal increase in the ecological status of a North-Atlantic intertidal seagrass meadow observed with multi-mission satellite time-series. (November 2021) - Zoffoli, Maria Laura; Gernez, Pierre; Godet, Laurent; Peters, Steef; Oiry, Simon; Barillé, Laurent
Highlights: Earth Observation (EO) provides consistent measurement of seagrass status. EO can complement field sampling within the Water Framework Directive (WFD). EO was used to map intertidal seagrass over 36 years with data every ≤ 3 years. EO time-series revealed increasing trend and high interannual fluctuations. Abstract: Seagrass meadows are monitored in the frame of several environmental programs worldwide, including the Water Framework Directive (WFD), to evaluate the ecological status of European coastal and transitional water bodies. The large size, spatial complexity, and interannual variability of seagrass ecosystems significantly challenge field monitoring. In this study, a multi-mission satellite time-series was used to estimate long-term changes in seagrass status in a macrotidal system dominated by Zostera noltei, at Bourgneuf Bay (French Atlantic coast). Metrics of seagrass extent and density were obtained from Earth Observation (EO) using validated and inter-calibrated Landsat, SPOT and Sentinel2 data from 1985 to 2020. The information provided by satellite data made it possible to compute and compare several seagrass indicators currently in use in several European countries (France, Portugal and UK) within the WFD. Both the seagrass extent and meadow-averaged density displayed increasing trends since 1985. A time-series of merged observations from various satellites revealed a high degree of interannual variability in seagrass extent, with abrupt losses (up to 50% within one year) alternating with periods of slow recovery (typically 4–6 years). The seagrass meadow which was in a moderate status ( sensu the WFD) in the 1980s, achieved an overall recurrent good or high status since the mid-1990s. Altogether, the methods and results presented here demonstrated that EO is a reliable source of information for mapping and assessing the status of intertidal seagrass, complementing in situ measurements by providing long-term, spatial view and standardized observation framework. We recommend the systematic use of EO time-series in complement to traditional field measurements in seagrass monitoring programs such as the WFD.